Laboratory determination of hydraulic anisotropy of dense graded asphalt concrete (2018)
Dense graded asphalt concrete is widely used in roads as support structure for vehicle loads. However, it is also used for hydraulic purposes in canal linings as well as faces and cores of dams. In the design stage of these constructions, it is necessary to have the permeability data of the materials that will be used and, although in some cases it is sufficient to know this parameter in only one direction, in others it is necessary to have it in two directions. The parameter that indicates the ratio of the permeability coefficients between the axial and transverse direction is known as hydraulic anisotropy (A). There are studies that estimate A in asphalt concrete, however, there is no standard procedure to determine these results in the laboratory. This research presents test results of axial permeability in constant head permeameter and the design of a radial permeability test device in asphalt concrete made for hydraulic purposes. As a result, it was determined that the compaction process of asphalt concrete, applied in one direction, causes the material to have anisotropic behavior from the hydraulic point of view, resulting in anisotropy ratios from 7.1 to 10.4, for the studied asphalt mixture. This research is of paramount importance for engineers who design hydraulic structures of asphalt concrete since it provides them with a simple laboratory procedure to determine the hydraulic anisotropy of this material.